Analysis of Patient Satisfaction in Mataram City, at the Start of the Pandemic Period, the Covid-19 Campaign - Nurul Hidayatai Indra Ningsih; Baiq Reinelda Tri Yunarti; Lalu Hendra Maniza (Jurnal Economic Resource, 2021)
The purpose of this study is to determine the degree of alignment between inpatient expectations and the quality of health services provided at Mataram City Regional General Hospital during the covid-19 pandemic. This study employs causal research techniques. Techniques for data collection that make use of questionnaires. The trial enrolled 82 patients. Purposive sampling was utilized in this investigation. In this study, quantitative analysis will be conducted using validity and reliability tests using Cronbach's Alpha. The t test, the f test, and the coefficient of determination are used to conduct hypothesis tests. IBM SPSS 25 computer application was used for testing. The t test revealed that the variables tangibility, reliability, responsiveness, assurance, and empathy) had a partial effect on patient satisfaction at Mataram City Regional General Hospital during the Covid-19 Pandemic. The f-test analysis revealed that the variables tangibility, reliability, responsiveness, assurance, and empathy) had a significant effect on patient satisfaction at Mataram City Regional General Hospital during the Covid-19 Pandemic. R2=648 in the determinant test. This suggests that tangibility, reliability, responsiveness, assurance, and emphaty had a 64.8 percent effect on patient satisfaction at Mataram City Hospital during the Covid-19 Pandemic era, while the remaining 35.2 percent is explained by other variables not included in this study.